The development of embedded positive input shaping for vibration control of a flexible manipulate using PIC - Yip, Hung Sum (2009)
This thesis presents investigation into the applications and performance of positive input shaping in command shaping techniques for the vibration control of a flexible robot manipulator. A constrained planar single-link flexible manipulator is considered and the dynamic model of the system is derived using the assume mode method and is explained. An unshaped bang-bang torque input is used to determine the characteristic parameters of the system for design and evaluation of the input shaping control techniques. The positive shaping technique is designed based on the properties of the system. Simulation result of the response of the manipulator to the shaped inputs form matlab simulation tools are presented in the time ·and frequency domains. Performances of the shapers are examined in terms of level of vibration reduction, time response specifications. The effects of derivations orders of the input shaper on the performance of the system are investigated. Next, the positive input shaping algorithm is embedded into PIC. Comparative of the PIC and simulation in matlab is presented. Finally, an analysis assessment of the impact amplitude polarities of the input shapers on the system performance is presented and discussed.